(untitled) (Práxis Educativa, 2022)
This article has as its goal to reflect on how educational practices and courseware present on Brazilian Basic Education traditionally thematize the indigenous cultures and to point out alternatives for the construction of an intercultural education that promotes the recognition and the dialogue with these people. For that, the hermeneutics as methodological approach is used. The discussion is founded on theorists of the decolonial thinking, as well as publications of indigenous authors. The article highlights the importance of a critical reflection about historical narratives and the conceptions of knowledge and ways of being and living. Finally, some of the errors commonly found in the approach of indigenous culture on schools are pointed out and alternatives for the development of intercultural pedagogical proposals are presented. Keywords: Intercultural education. Interculturality. Indigenous thematic.